Surveillance, control and management of infections in intensive care units in Southern Europe, Turkey and Iran - A prospective multicenter point prevalence study - KORTEN, VOLKAN (W B SAUNDERS CO LTD, 2014)
Objective: We aimed to compare the features of intensive care units (ICUs), their antimicrobial resistance patterns, infection control policies, and distribution of infectious diseases from central Europe to Mid-West Asia. Methods: A cross-sectional point prevalence study was performed in 88 ICUs from 12 countries. Characteristics of ICUs, patient and antibiotic therapy data were collected with a standard form by infectious diseases specialists. Results: Out of 749, 305 patients at least with one infectious disease were assessed and 254 patients were reported to have coexistent medical problems. When primary infectious diseases diagnoses of the patients were evaluated, 69 had community-acquired, 61 had healthcare-associated, and 176 had hospital-acquired infections. Pneumonia was the most frequent ICU infection seen in half of the patients. Distribution of frequent pathogens was as follows: Enteric Gram-negatives (n = 62, 28.8%), Acinetobacter spp. (n = 47, 21.9%), Pseudomonas aeruginosa (n = 29, 13.5%). Multidrug resistance profiles of the infecting microorganisms seem to have a uniform pattern throughout Southern Europe and Turkey. On the other hand, active and device-associated infection surveillance was performed in Turkey more than Iran and Southeastern Europe (p < 0.05). However, designing antibiotic treatment according to culture results was highest in Southeastern Europe (p < 0.05). The most frequently used antibiotics were carbapenems (n = 92, 30.2%), followed by anti-gram positive agents (vancomycin, teicoplanin, linezolid, daptomycin, and tigecycline; n = 79, 25.9%), beta-lactam/beta lactamase inhibitors (n = 78, 25.6%), and extended-spectrum cephalosporins (n = 73, 23.9%). Conclusion: ICU features appears to have similar characteristics from the infectious diseases perspective, although variability seems to exist in this large geographical area. (C) 2013 The British Infection Association. Published by Elsevier Ltd. All rights reserved.
Keywords: ICU; Infection; Turkey; Europe; Iran; Resistance; DISEASES; OUTCOMES; RESISTANCE; COUNTRIES; MORTALITY; BACTERIA; PATIENT; IMPACT